Killinek, Eskimofrauen in Festtracht : [19--] - Hettasch, Paul, 1873-1949. (2001)
Black and white photograph of a group of Inuit women of Killinek dressed in festive clothing. Black and white photograph of a group of Inuit women of Killinek dressed in festive clothing.